2021
DOI: 10.1098/rspb.2021.0812
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evolution can enhance benefits of rhizobia to novel legume hosts

Abstract: Legumes preferentially associate with and reward beneficial rhizobia in root nodules, but the processes by which rhizobia evolve to provide benefits to novel hosts remain poorly understood. Using cycles of in planta and in vitro evolution, we experimentally simulated lifestyles where rhizobia repeatedly interact with novel plant genotypes with which they initially provide negligible benefits. Using a full-factorial replicated design, we independently evolved two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…Empirical evidence supporting conflict or alignment in symbiotic mutualisms is mixed: when examining relationships between host and symbiont fitness proxies, some studies have observed an overall negative (4,25,26) while others have found a positive (15,27) correlation. Recent experimental evolution studies (28)(29)(30) have failed to detect the evolution of cheaters and instead found that microbial adaptation to particular host genotypes is associated with an increase, rather than a decrease, in partner quality, i.e., the fitness benefit a symbiont genotype confers to its host.…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence supporting conflict or alignment in symbiotic mutualisms is mixed: when examining relationships between host and symbiont fitness proxies, some studies have observed an overall negative (4,25,26) while others have found a positive (15,27) correlation. Recent experimental evolution studies (28)(29)(30) have failed to detect the evolution of cheaters and instead found that microbial adaptation to particular host genotypes is associated with an increase, rather than a decrease, in partner quality, i.e., the fitness benefit a symbiont genotype confers to its host.…”
Section: R a F Tmentioning
confidence: 99%
“…1A). Evidence for fitness conflict within mutualism is mixed: although several studies have identified symbiont genotypes that gain fitness at their host's expense (e.g., 18,19), recent experimental evolution studies instead found that microbial adaptation to particular host genotypes is associated with an increase, rather than a decrease, in host fitness (20)(21)(22). Yet, fitness alignment at the phenotypic level does not necessarily preclude fitness conflict at the genomic level: rather than dichotomous categories of "cooperator" or "cheater", mutualist genomes are best viewed as mosaics of loci (5), some underlying cooperation while others underlie conflict.…”
Section: R a F Tmentioning
confidence: 99%
“…Several experiments indicate that expanding host ranges relies on the accumulation of multiple mutations, which is less likely, and requires more time, than a single mutation (Hall et al, 2011 ; Longdon et al, 2014 ; Meyer et al, 2012 ; Quides et al, 2021 ; Soto et al, 2019 ; Streicker et al, 2012 ; Woolhouse et al, 2005 ). Because we selected on nematode emergence, mutations that increase nematode survival or reproduction should be favored.…”
Section: Discussionmentioning
confidence: 99%
“…Future functional analyses of the adaptive mutations identified in this study will expand our understanding of the molecular bases of nodulation competitiveness in rhizobia 60,71,72 , and its relationship to within-host proliferation. Including mutualistic traits (nitrogen fixation and host growth promotion) in the analysis of the genetic couplings (or trade-offs) between the different symbiotic traits will be important to fully characterize the genetic constraints shaping the evolution of rhizobium-legume interactions [72][73][74] . The genetic links between different host colonization phases are generally poorly documented in other symbiotic systems, but they were analyzed in two recent experimental evolution studies with opposite outcomes.…”
Section: Discussionmentioning
confidence: 99%